El Paleolítico medio en el Próximo Oriente. Una síntesis regional - Domínguez-rodrigo, Manuel; Torre Sáinz, Ignacio De La (Complutum, 2000)
The archaeological evidence from the Middle Paleolithic in the Near East is summed up in this work. It is embodied in the Late Middle Pleistocene and the Early Upper Pleistocene. We present a summary of the main sites, the chronologies and the most important lithic facies from a regional perspective. We divided the archaeological record according to three different ecological regions: the mediterranean zone, the continental zone and the mountain zone.